Sentidos significados e saberes escolares frente à exploração da bauxita na Amazonia - Galvao, Juarez Bezerra (2014)
This text production aims to present senses, meanings and knowledge of school subjects across the mining project in Juruti, Amazon, analyzing the impact of Alcoa's project for education and Juruti County in western Pará as mining activity production grew at expanded their domains in Brazil in the last 20 years playing the discourse of development with sustainability. However, there are many differences regarding the effectiveness of this speech, given the large social - cultural - political - environmental that mining activities cause and continue to cause, especially in countries with weak control actions and penalties for crimes against impacts environment. ALCOA, a U.S. company engaged in the extraction of bauxite, was installed in Juruti County, State of Pará in 2003, with a future perspective to implement a plant for the production of alumina and aluminum in the Amazon. The deployment of the company did not give a harmonic way, because different social groups engaged in actions to derail its implementation in the region. This scenario prompted us to study more deeply the perspective of critical theory reconceptualized the educational reality in the city amid the interference of mining. It is a thesis of qualitative methodological approach to data collection we employed the semi - structured interviews, direct observation and application of targeted questionnaires to the following subjects: managers and coordinators of SEMED, the directors of the Municipal Board of Education (CME); director , teaching coordination, faculty and staff of the schools included in the study. Focus groups were held with representatives of students in participating schools ; closed questionnaires addressed to students and parents; document analysis and participant observation of everyday school life. We believe that this thesis contributes to the debate about the exploitation of the Amazon, as well as the role of education in this context